Comparative study of programmed labor and traditional management of labor - Kshirsagar, Nitin S.; Patil, Sanjay S.; Karale, Anand V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Prolongation of labor leads to dehydration, ketoacidosis, infection, fetal asphyxia. Programmed labor aims at reducing the duration of labor, labor pain and incidence of cesarean section with improved maternal and neonatal outcome. Aims and Objectives: 1) To evaluate the effect of programmed labor on duration of labor. 2) To assess efficacy of analgesics in reducing pain of labor. 3) To find out maternal and neonatal complications. 4) To study impact of programmed labor on LSCS rates. Methods: Prospective randomized study of primigravida in active labor (after 4 cm cervical dilatation) for which 100 women were selected for programmed labor (cases) and 100 women were selected for traditional management of labor (controls). Cases were subjected to interventions to improve uterine contractions (ARM, Dinoprostone tablets, and Oxytocin drip), to facilitate cervical dilatation (Inj. Drotaverine), to relieve labor pains (Inj. Pentazocine & Diazepam). All labors were monitored by partogram. Results: Programmed labor reduced duration of first and second stage of labor. There was faster cervical dilatation (1.8 cm/hour against 1.2 cm/hour). Majority of the patients had better pain relief. There was no impact on LSCS rates Conclusions: Programmed labor significantly reduced duration of labor with good pain relief without compromising maternal and fetal/neonatal safety. But it had no impact on LSCS rates.